2010
DOI: 10.1089/aid.2009.0154
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Plasma Concentrations of the HIV Protease Inhibitor Lopinavir

Abstract: The advent of highly active antiretroviral therapy in the treatment of HIV disease has substantially extended the lifespan of individuals infected with HIV resulting in a growing population of older HIV-infected individuals. The efficacy and safety of antiretroviral agents in the population are important concerns. There have been relatively few studies assessing antiretroviral pharmacokinetics in older patients. Thirty-seven subjects aged 18-30 years and 40 subjects aged 45-79 years, naive to antiretroviral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…Although these events were not independently adjudicated, they were collected prospectively according to protocol-specified definitions. Also consistent with several other studies, we previously reported that medication adherence was better in older patients, which may have accounted for the lower rate of viral load rebound that we observed in older patients [40]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although these events were not independently adjudicated, they were collected prospectively according to protocol-specified definitions. Also consistent with several other studies, we previously reported that medication adherence was better in older patients, which may have accounted for the lower rate of viral load rebound that we observed in older patients [40]. …”
Section: Discussionsupporting
confidence: 92%
“…Although we previously reported no significant age group differences in grade 3 or 4 medication-associated toxicities [40], it is possible that stavudine use may have contributed to a greater risk of mitochondrial dysfunction in older patients since age is a strong risk factor for nucleoside analog-associated lipodystrophy [41], a complication that has been associated with reduced mitochondrial (mt)DNA content [42]. Previous studies have identified significant differences in mtDNA according to prior nucleoside analog exposure [43].…”
Section: Discussionmentioning
confidence: 99%
“…Because the aging HIV population is increasing, few PIs have been studied in the elderly. [3][4][5] The Bristol-Myers Squibb Company (BMS) product information 3 and von Hentig et al 5 reported that age does not influence atazanavir concentrations. However, both studies were conducted in a white population.…”
Section: Introductionmentioning
confidence: 99%
“…Three prospective studies assessing the PK effects of ARVs in older HIV‐infected patients were identified . A study evaluated the exposure of two alternative first‐line regimens in 12 HIV‐infected adults aged 55 years or older (mean age 59.7 ± 3.9 yrs) in an unblinded, intensive‐sampling PK study.…”
Section: Pharmacokineticsmentioning
confidence: 99%